2021
DOI: 10.51470/plantarchives.2021.v21.no1.130
|View full text |Cite
|
Sign up to set email alerts
|

Phytoproduction of Iron Nanoparticles for Methyl Orange Removal and Its Optimization Studies

Abstract: In the present study, iron nanoparticles have been synthesized using the leaf extract of potential weed Datura inoxia to evaluate their feasibility for methyl orange removal. This method approves that the green synthesis method must be adopted for the more efficient and rapid synthesis of metal nanoparticles. A simple process of bio reduction has been involved, the leaf extract of Datura inoxia used as a precursor for reducing metal iron. The UV- visible spectral analyses for iron nanoparticles have shown a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 47 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The FeNPs were separated from the solution through centrifugation at 15000 rpm. FeNPs were kept in an incubator at 35 o C (11,12) .…”
Section: Green Synthesis Of Di-fenpsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FeNPs were separated from the solution through centrifugation at 15000 rpm. FeNPs were kept in an incubator at 35 o C (11,12) .…”
Section: Green Synthesis Of Di-fenpsmentioning
confidence: 99%
“…The batch studies done for optimization of MO dye removal were applied in RSM (12) . pH was set using HCl (0.1N) and NaOH (0.1N).…”
Section: Green Synthesis Of Di-fenpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RL values reflect the isotherm type; if RL > 1, the isotherm is unfavourable; if RL = 1, the isotherm is favourable and if RL = 0, the isotherm is irreversible. The current results (RL value) 0.027 indicating that adsorption was favourable [19][20][21].…”
Section: Langmuir Equilibrium Isothermmentioning
confidence: 99%
“…9) and are reported in Table 1. The data showed that this adsorption fits the Langmuir isotherm model better than the Freundlich isotherm model [19][20][21].…”
Section: Freundlich Isothermmentioning
confidence: 99%